Tax Compliance Cost Burden and Tax Perceptions Survey in Ethiopia - World Bank Group (World Bank, Washington, DC, 2016)
This study attempts to estimate tax compliance costs and assess views of taxpayers on aspects of the tax system in Ethiopia. The study uses evidence mainly from a survey of both formal and informal businesses in Addis Ababa and four major cities (Adama, Hawassa, Mekele, and Bahir Dar) in the four largest regional states. The survey covered 1003 formal businesses and 499 informal businesses. Survey questionnaires were informed by the results of four focus group discussions conducted in Addis Ababa and Adama. The findings of the study are expected to offer tax policy makers and tax administrators an opportunity to pinpoint specific problems to help reduce the cost of complying with tax policies and procedures, thus improving the revenue performance and also the efficiency and business-friendliness of the tax system. The report is organized in four sections. The first part presents an overview of the Ethiopian tax system and recent reform initiatives; second section discusses the research objectives and the methods employed. Section three presents results of the survey while section four presents conclusions and recommendations.